2021
DOI: 10.1038/s41598-021-02768-0
|View full text |Cite
|
Sign up to set email alerts
|

A food web approach reveals the vulnerability of biocontrol services by birds and bats to landscape modification at regional scale

Abstract: Pest control services provided by naturally occurring species (the so-called biocontrol services) are widely recognized to provide key incentives for biodiversity conservation. This is particularly relevant for vertebrate-mediated biocontrol services as many vertebrate species are of conservation concern, with most of their decline associated to landscape modification for agricultural purposes. Yet, we still lack rigorous approaches evaluating landscape-level correlates of biocontrol potential by vertebrates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The local landscape surrounding agricultural fields may also influence the level of avian predation. Several studies supported that avian predation was highest in agricultural fields surrounded by or adjacent to woody areas (Puckett et al 2009, Milligan et al 2014, García et al 2018, Herrera et al 2021, Lourenço et al 2021. In contrast, predation decreased in agricultural fields surrounded by few to no forest fragments (Milligan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The local landscape surrounding agricultural fields may also influence the level of avian predation. Several studies supported that avian predation was highest in agricultural fields surrounded by or adjacent to woody areas (Puckett et al 2009, Milligan et al 2014, García et al 2018, Herrera et al 2021, Lourenço et al 2021. In contrast, predation decreased in agricultural fields surrounded by few to no forest fragments (Milligan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While we did not observe any difference in HIPV treatments, we did measure appreciable levels of bird attacks on our caterpillars. In an effort to reduce the use of pesticides in agricultural settings, the efficacy of bird predation as a natural form of biocontrol has been demonstrated in many agricultural contexts (Puckett et al 2009, Milligan 2014, García et al 2018, reviewed in Díaz-Siefer et al 2021, Herrera et al 2021, Lourenço et al 2021), but not all (Martínez-Núñez et al 2020). These recent studies have shown promising data that bird predation could be an alternative form of pest control that can be artificially exploited, for example using nest boxes (Mols and Visser 2007, Koh 2008, Olmos-Moya et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, ours and previous studies suggest that impacts of intensification could be less pronounced in orchards with reduced use of agrochemicals and with a more developed herbaceous layer 13 , 94 , though the feasibility and consequences of implementing such practices in intensive and superintensive orchards is still uncertain. Likewise, there is some support for the importance of maintaining semi-natural habitats at the landscape scale to reduce biodiversity impacts and pest abundance within orchards 25 , 101 , but quantification of the amount and types of habitats required to achieve such goals is still lacking. Overall, our results suggest that the rapid expansion of intensive and superintensive orchards is negatively impacting arthropod communities that inhabit Mediterranean farmland.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their insectivorous diet, European bats represent efficient natural enemies of many pest insects (Aizpurua et al, 2018;Herrera et al, 2021) that could potentially exert top-down pest control (Russo et al, 2018). However, bats have shown marked population declines that are believed to have occurred during the second half of the twentieth century in Europe (Browning et al, 2021) and many species are still threatened with extinction (IUCN, 2021).…”
Section: Introductionmentioning
confidence: 99%